The Concept of Madrasah Education During the Abbasid Period - Nurul Amaliyah; Ahmad Kausari (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to explore and understand in depth the concept of education that developed during the reign of the Abbasid Caliphate, a period known as the golden age in the history of Islamic civilization. During this period, education and science experienced very rapid progress, marked by the development of various branches of science, both Islamic and general. This study uses a library study approach with a descriptive method, namely an approach that focuses on the review of various relevant literature, documents, and historical references to obtain a comprehensive picture of the education system during that period. The results show that the concept of education during the Abbasid era strongly emphasized the balance between religious knowledge and general knowledge. Islamic knowledge remained the main foundation, but did not close itself off from the development of other sciences such as philosophy, medicine, mathematics, and astronomy. The Abbasid government paid great attention to the world of education, including in terms of funding, the construction of educational institutions, and appreciation for scientists. Strong state support and openness to receiving knowledge from various civilizations were important factors in making this era a milestone in educational progress in Islamic history.